2016
DOI: 10.1523/jneurosci.4421-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Role of Binaural Temporal Fine Structure and Envelope Cues in Cocktail-Party Listening

Abstract: While conversing in a crowded social setting, a listener is often required to follow a target speech signal amid multiple competing speech signals (the so-called "cocktail party" problem). In such situations, separation of the target speech signal in azimuth from the interfering masker signals can lead to an improvement in target intelligibility, an effect known as spatial release from masking (SRM). This study assessed the contributions of two stimulus properties that vary with separation of sound sources, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…They retained or removed ITD-based cues of spatial separation in the TFS by vocoding with either the same or uncorrelated noises at each ear, respectively. Swaminathan et al (2016) found that correlated-noise vocoding produced similar SRTs and SRM to non-vocoded stimuli, but vocoding with interaurally uncorrelated noises produced poorer SRTs and SRM. The effect of noise vocoding on SRM was predominantly driven by the interaural correlation of the noise carriers below 1.5 kHz.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…They retained or removed ITD-based cues of spatial separation in the TFS by vocoding with either the same or uncorrelated noises at each ear, respectively. Swaminathan et al (2016) found that correlated-noise vocoding produced similar SRTs and SRM to non-vocoded stimuli, but vocoding with interaurally uncorrelated noises produced poorer SRTs and SRM. The effect of noise vocoding on SRM was predominantly driven by the interaural correlation of the noise carriers below 1.5 kHz.…”
Section: Introductionmentioning
confidence: 91%
“…This extra elevation suggests that binaural TFS cues, even carried by TVC signals, can help speech intelligibility. More recent evidence suggests a greater role of binaural TFS cues and a smaller role of the original speech TFS: Swaminathan et al (2016) studied the effect on SRM of noise vocoding before convolving speech with HRIRs. They retained or removed ITD-based cues of spatial separation in the TFS by vocoding with either the same or uncorrelated noises at each ear, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…One likely reason for the reduced spatial benefit for HI users is that they have limited access to sound localization cues on the horizontal plane such as interaural time difference (ITD) and interaural level difference (ILD) cues. Previous studies have shown that ITD sensitivity is particularly important for localization performance and speech perception in noise (Gifford et al, 2013;Swaminathan et al, 2016;Ellinger et al, 2017). Phase-locking and ITD sensitivity can both be impaired with hearing loss (Henry and Heinz, 2013;Dai et al, 2018).…”
Section: Speech Release From Masking In Nh and Hi Listenersmentioning
confidence: 99%
“…Adequate processing of both envelope and TFS information is indispensable for speech understanding ( Swaminathan & Heinz, 2012 ; Zeng et al., 2005 ). Moreover, binaural TFS processing underlies spatial release from masking, that is, a binaural advantage that results in improved speech understanding when a speech target is spatially separated from interfering sound streams ( Swaminathan et al., 2016 ). This study was designed to gain more insight in age- and HI-related changes in binaural TFS processing throughout adult life.…”
Section: Introductionmentioning
confidence: 99%